2015
DOI: 10.1016/j.jnutbio.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of vitamin D2 enhanced mushrooms is associated with improved bone health

Abstract: Mushrooms are the best nonanimal food source of vitamin D2. Pulsed irradiation can enhance vitamin D2 in mushrooms quickly. We investigated the effect of supplementing high vitamin D2Pleurotus ferulae mushrooms in a mouse model of osteoporosis. Thirty-two female C57BL/6JNarl mice were divided into four groups including sham, ovariectomized (OVX), OVX+nonpulsed mushroom (NPM) and OVX+pulsed mushroom (PM). After 23 weeks of treatment, serum samples were analyzed for osteoblast and osteoclast indicators, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 53 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…In 27 participants with a baseline mean serum 25(OH)D concentration of 38.5 nmol/L, vitamin D 2 from mushrooms increased serum 25(OH)D concentrations as effectively as a vitamin D 2 supplement after three weeks. Since then, the bioavailability of vitamin D 2 from mushrooms has been demonstrated in both rats [ 36 , 63 , 64 ] and humans [ 10 , 65 , 66 , 67 , 68 ], and there is evidence that vitamin D 2 from mushrooms supports bone health in animal models [ 47 , 64 , 69 , 70 ].…”
Section: Bioavailability Of Vitamin D 2 From Mumentioning
confidence: 99%
“…In 27 participants with a baseline mean serum 25(OH)D concentration of 38.5 nmol/L, vitamin D 2 from mushrooms increased serum 25(OH)D concentrations as effectively as a vitamin D 2 supplement after three weeks. Since then, the bioavailability of vitamin D 2 from mushrooms has been demonstrated in both rats [ 36 , 63 , 64 ] and humans [ 10 , 65 , 66 , 67 , 68 ], and there is evidence that vitamin D 2 from mushrooms supports bone health in animal models [ 47 , 64 , 69 , 70 ].…”
Section: Bioavailability Of Vitamin D 2 From Mumentioning
confidence: 99%
“…One of the first attempts to use NMR in human nutrition was related to the investigation of the impact of soy isoflavone consumption on the biochemical composition of urine (Solanky et al., ). Since then, several nutrition‐related applications of NMR have been reported, mainly focusing on identifying changes in the metabolome as a result of a nutritional approach (Bondia‐Pons et al., ; Chen et al., ; Lehtonen et al., ; Rådjursöga et al., ) or an individual food ingredient (Barbaro et al., ; Massimi et al., ; Picone et al., ). Characteristic projects involve the investigation of the effects of dark chocolate consumption on human metabolism (Martin et al., ), the nutritional intervention of tomato sauce (Bondia‐Pons et al., ), the effect of low and high dairy intake in overweight women (Zheng et al., ), studying the associations between dietary influences and cultural differences (Lenz et al., ), investigating the effects of vegetarian, low meat, and high meat diets (Stella et al., ), and the effects of consuming a Mediterranean diet (Vázquez‐Fresno et al., ).…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%
“…In related studies, (a) Sławińska, et al [ 247 ] reported that after 1.5 year storage of dried Agaricus bisporus UV-B mushrooms, the vitamin D2 content was decreased by 48.32% of the initial level; (b) Mehrotra, et al [ 248 ] describe unanticipated losses of D2 during cooking from fresh UV-B mushrooms; and (c) Calvo, et al [ 249 ], Chen, et al [ 250 ], and Simon, et al [ 251 ] found that the vitamin D in mushrooms, produced by exposure to UV light, seemed to be bioavailable and safe.…”
Section: Additional Health Benefitsmentioning
confidence: 99%